Cornerstones of a sustainable national quality policy: A qualitative study based on international expert opinions. (18th August 2022) - Brouwers, Jonas; Claessens, Fien; Castro, Eva Marie; Van Wilder, Astrid; Eeckloo, Kristof; Bruyneel, Luk; De Ridder, Dirk; Vanhaecht, Kris
Abstract: Background: National initiatives launched to improve the quality of care have grown exponentially over the last decade. Public reporting, accreditation and governmental inspection form the basis for quality in Flemish (Belgian) hospitals. Due to the lack of evidence for these national initiatives and the questions concerning their sustainability, our research aims to identify cornerstones of a sustainable national quality policy for acute‐care hospitals based on international expert opinion. Methods: A qualitative study was conducted using in‐depth semi‐structured interviews with 12 renowned international quality and patient safety experts selected by purposive sampling. Interviews focussed on participants' perspectives and their recommendations for a future, sustainable quality policy. Inductive analysis was carried out with themes being generated from the data using the constant comparison method. Results: Three major and five minor themes were identified and integrated into a framework as a basis for national quality policies. Quality culture, minimum requirements for quality education and quality control as well as continuous learning and improvement act as cornerstones of this framework. Conclusions: Complementary to the current national policy, this study demonstrated the need for profound attention to quality cultures in acute‐care hospitals. Policymakers need to provide a control system and minimum requirements for quality education for all healthcare workers. A model for continuous learning and improvement with data feedback loops has to be installed in each hospital to obtain a sustainable quality system. This framework can inspire policymakers to further develop bottom‐up initiatives in co‐governance with all relevant stakeholders adapted to individual hospitals' context. Highlights: A sustainable national quality policy focuses on major cornerstones: quality culture, minimal requirements and continuous learning and improvement. Major cornerstones are described with minor ones to face current challenges in healthcare quality. A future quality policy is not a 'one‐size‐fits‐all' approach, but need to be adapted to individual hospitals' context and the maturity of their quality system. The proposed framework can inspire policymakers to develop quality initiatives bottom‐up.